A charge steering type digital analog converter - Ikari, J.; Nakamura, S.; Nagazumi, Y. (2007 50th Midwest Symposium on Circuits and Systems, 2007)
In this paper we propose new type of D/A converters implemented by charge steering operations. The basic structure of the converter is a series of overlapping gates that can operate on charge along its steering path. The designs were fabricated by a standard 1.5 um CMOS process. Results from their evaluation experiments are presented. By a simple charge accumulation method more than 11-bit of resolution is observed. For D/A conversion by successive charge splitting, the resulting resolution is 5-bit with a power consumption of 8 pJ/bit. The splitting accuracy of the charge splitters of different size is also evaluated.